Identifying the anatomical and physiological restrictions imposed by sickle cell anemia in adolescence (Research, Society and Development, 2024)
This study aims to identify the anatomophysiological restrictions imposed by sickle cell anemia in adolescence. The methodology used was an integrative literature review, covering scientific articles published between 2018 and 2024 on the SCIELO, VHL, and PUBMED databases. Twenty-five articles related to the topic were included. The results indicate that adolescents with sickle cell anemia face various complications, such as vessel-occlusive crises, tissue damage, difficulties in physical development, and cognitive problems. These complications affect physical and mental health, resulting in social isolation and difficulties in academic and professional life. In addition, the limitations imposed by the disease harm young people's quality of life. The conclusion highlights the importance of early diagnosis, continuous monitoring, and appropriate interventions to minimize the disease effects and improve the quality of life of affected adolescents. Treatment with hydroxyurea and public policies that promote access to healthcare are fundamental to managing the disease and reducing complications. Collaboration between health professionals, families, and society is essential to guarantee support for those with sickle cell anemia.